Analytical characteristic equation for partially covered photovoltaic thermal (PVT) compound parabolic concentrator (CPC). (January 2015) - Atheaya, Deepali; Tiwari, Arvind; Tiwari, G.N.; Al-Helal, I.M.
Highlights: Thermal modeling of a partially covered photovoltaic thermal-compound parabolic concentrator (PVT-CPC) has been developed. An analytical expression for electrical efficiency of PVT-CPC has been derived. The characteristic equation for PVT-CPC has also been developed. The exergy analysis of PVT-CPC system for different configurations has been carried out. Abstract: In this paper, an analytical expression for characteristic equation of a partially covered photovoltaic thermal compound parabolic concentrator (PVT-CPC) water collector system similar to Hottel–Whillier–Bliss (HWB) equation of flat plate collector has been derived. The derivation is based on basic energy balance equation for each component of partially covered PVT-CPC water collector system. The analytical result of proposed partially covered PVT-CPC water collectors [case (i)] has been compared with [case (ii)]: fully covered PVT-CPC water collectors; [case (iii)]: conventional CPC water collectors and [case (iv)]: partially covered PVT water collectors. It is observed that (a) an overall exergy efficiency of partially covered PVT-CPC water collector (25%PV) system is maximum and (b) an instantaneous thermal efficiency of conventional CPC water collector system [case (iii)] is maximum as compared to other cases.